Self-reported obstructive sleep apnea, amyloid and tau burden, and Alzheimer’s disease time-dependent progression - Bubu, Omonigho M. (Alzheimers Dement, 2020)
INTRODUCTION: Obstructive Sleep Apnea (OSA) is associated with Alzheimer’s disease (AD) biomarkers in cognitive normal (CN) and mild cognitive impaired (MCI) participants. However, independent and combined effects of OSA, Aβ and tau-accumulation on AD time-dependent-progression risk is unclear. METHODS: Study participants grouped by biomarker profile, as described by the A/T/N scheme, where “A” refers to aggregated Aβ, “T” aggregated tau and “N” to neurodegeneration, included 258 CN (OSA+ [A+TN+ n=10, A+/TN− n=6, A−/TN+ n=10, A−/TN− n=6 and OSA− [A+TN+ n=84, A+/TN− n=11, A−/TN+ n=96, A−/TN− n=36]) and 785 MCI (OSA+ [A+TN+ n=35, A+/TN− n=15, A−/TN+ n=25, A−/TN− n=16 and OSA− [A+TN+ n=388, A+/TN− n=28, A−/TN+ n=164, A−/TN− n=114]) older-adults from Alzheimer’s Disease Neuroimaging Initiative cohort. Cox proportional hazards regression models estimated the relative hazard of progression from CN-to-MCI and MCI-to-AD, among baseline OSA CN and MCI-patients respectively. Multi-level logistic mixed-effects models with random intercept and slope investigated the synergistic associations of self-reported OSA, Aβ and Tau burden with prospective cognitive decline. RESULTS: Independent of TN-status (CN and MCI), OSA+/Aβ+ participants were approximately two to four times more likely to progress to MCI/AD (p<.001) and progressed six to eighteen months earlier (p<.001), compared to other participants combined (i.e. OSA+/Aβ−, OSA−/Aβ+ and OSA−/Aβ−). Notably, OSA+/Aβ− vs. OSA−/Aβ− (CN and MCI) and OSA+/TN− vs. OSA−/TN− (CN) participants showed no difference in the risk and time-to-MCI/AD progression. Mixed effects models demonstrated OSA synergism with Aβ (CN and MCI [β=1.13, 95%CI, 0.74 to 1.52, and β = 1.18, 95%CI, 0.82 to 1.54]) respectively, and with tau ([MCI (β = 1.31, 95%CI, 0.87 to 1.47)], p< 0.001 for all. DISCUSSION: OSA acts in synergism with Aβ and with tau, and all three acting together result in synergistic neurodegenerative mechanisms especially as Aβ and tau-accumulation becomes increasingly-abnormal, thus leading to shorter progression time-to-MCI/Alzheimer’s disease (AD) in CN and MCI-OSA patients respectively.